Practice on edge cloud security of telecom operators - Le ZHANG; Hongyuan MA (Dianxin kexue)
Abstact: In the peak period of operator edge cloud construction, in order to realize the “three synchronization” construction strategy, the network edge cloud construction and operation and maintenance management mode were expounded, the security risks and security construction requirements of network edge cloud were discussed firstly.Then, the limitations of the security construction mode in the edge cloud scenario for the traditional cloud were analyzed.Finally, an innovative network edge cloud security construction plan was proposed, and the province’s edge cloud security construction was carried out uniformly.The comparison was completed from the perspective of practical application, and the advantages of the innovative edge cloud construction plan was verified.